18F-PSMA-1007 multiparametric, dynamic PET/CT in biochemical relapse and progression of prostate cancer - Sachpekidis, Christos; Afshar-Oromieh, Ali; Kopka, Klaus; Strauss, D. S.; Pan, L.; Haberkorn, Uwe; Dimitrakopoulou-Strauss, Antonia (European journal of nuclear medicine and molecular imaging, 2020)
Aim of the present analysis is to investigate the biodistribution and pharmacokinetics of the recently clinically introduced radioligand 18F-PSMA-1007 in patients with biochemical recurrence or progression of prostate cancer (PC) by means of multiparametric (dynamic and whole-body) PET/CT.
Im Titel ist die Zahl 18 hochgestellt
Published online: 14 November 2019
Gesehen am 02.04.2020